Pengaruh Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian Brand Sepatu Ortuseight - Hari Arizky; Tina Lestari; Abdul Kadir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to ascertain the extent to which the Ortuseight Shoe Brand's purchasing decision is influenced by Product Quality, Price, and Promotion. This study's general population consists of 56 respondents from the Banjarmasin Futsal STIE Pancasetia UKM in 2021-2024. Reviews with different straight backslides utilizing spss 027 were utilized to accumulate information. The study reveals that the Ortuseight Shoe Brand Purchase Decision is significantly influenced by the Promotion variable, but not by the Price variable or the Product Quality variable. Product quality, price, and promotion all have a significant impact on the Ortuseight Shoe Brand's decision to buy. Additionally, the Ortuseight Shoe Brand Purchase Decision is significantly influenced by the Product Quality variable